Analysis of Malaria Control Situation in Magelang Regency and Obstacles to Maintain Malaria Elimination Status - Ahmad, Nasir; Isworo, Adi; Indriani, Citra (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Magelang Regency received malaria elimination certificate in April 2014, however, the epidemic signal was received back in April 2015. Malaria epidemic had occurred for two months and until the end of December, indigenous cases could still be found. The purpose of this study was to find out description of situation regarding malaria, malaria control, and obstacles to malaria control in Magelang Regency. Rapid assessment method was conducted by adopting the methodology in the protocol and methods for malaria situation analysis from WHO (2003) and by using desk review as the reference for the research process in malaria control method in a region with similar condition to Magelang regency. Data collection was performed through interview and observation. This study found that in April 2015, the number of indigenous cases was 2 which was increased to 37 cases in May and the peak prevalence was 56 cases in June. Previously, import cases were found in March. Up until December, malaria cases were dominated by indigenous cases (97%). Village regulation regarding malaria migration surveillance was still not available in most receptive villages. In area which had eliminate malaria, there should be regulation that govern malaria migration surveillance. Therefore, the Regent should advise the village chief through a circulatory letter to form a new regulation regarding malaria migration surveillance in order to reduce outbreak potential.